PENGARUH PUPUK MAJEMUK TERHADAP PRODUKSI DAN MUTU TEMBAKAU VIRGINIA / Effect of Compound Fertilizer on Yield and Quality of Virginia Tobacco - Djajadi Djajadi; Sulis Nur Hidayati; Roni Syaputra (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
Tobacco Generally farmers in Lombok apply single fertilizer of ZA or Urea (as a source of N), and SP36 (as source of P), without combining with K and Mg fertilizers. The fertilizers are added more than twice with unappropriates doses. Application of compound fertilizer might increase growth, yield and quality of Virginia fc tobacco at Central Lombok, West Nusa Tenggara Province, because the fertilizer consists of NPK macro nutrients which have important role for tobacco. The experiment was carried out at Kopang Rembiga village, Kopang District in 2014. The objective to was identify the effect of NPKMg compound fertilizer on growth, yield and quality of Virginia tobacco. Split Plot Design with three replicates was used to arrange treatments. Three varieties of Virginia tobacco (Coker 176, Coker 319 and NC 297) were set as main plots, and three rates of NPKMg fertilizer (60, 80 and 100 kg N/ha) were arranged as sub plots. Results showed that increasing of NPKMg fertilizer up to 100 kg N/ha increased growth, yield and quality of three varieties of Virginia tobacco. Addition of 100 kg N/ha NPKMg (100 kg N+ 60 kg P2O5 + 133 kg K2O + 13.34 kg MgO per hectare) gave the highest values of grade index and crop index of three varieties, thus the fertilizer could be recommended for Virginia tobacco in Lombok.